2018
DOI: 10.3390/ph11030089
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Friedreich Ataxia: A Central Role in the Pathophysiology or an Epiphenomenon?

Abstract: Friedreich ataxia is a neurodegenerative disease with an autosomal recessive inheritance. In most patients, the disease is caused by the presence of trinucleotide GAA expansions in the first intron of the frataxin gene. These expansions cause the decreased expression of this mitochondrial protein. Many evidences indicate that frataxin deficiency causes the deregulation of cellular iron homeostasis. In this review, we will discuss several hypotheses proposed for frataxin function, their caveats, and how they co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 97 publications
(123 reference statements)
1
34
0
Order By: Relevance
“…Friedrich's Ataxia is probably the most common form of this type of neurological diseases. Friedreich ataxia is a genetic disease caused by the deficiency of frataxin, a mitochondrial protein supposed to work such as a metal chaperone and iron storage protein [116]. Frataxin-deficient cells were often observed to be highly sensitive to oxidizing agents [117,118].…”
Section: Ros and Ataxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Friedrich's Ataxia is probably the most common form of this type of neurological diseases. Friedreich ataxia is a genetic disease caused by the deficiency of frataxin, a mitochondrial protein supposed to work such as a metal chaperone and iron storage protein [116]. Frataxin-deficient cells were often observed to be highly sensitive to oxidizing agents [117,118].…”
Section: Ros and Ataxiamentioning
confidence: 99%
“…However, looking at the mitochondrial iron pools, no differences were observed between controls or Friedrick's ataxia in human lymphoblasts or fibroblasts [119]. Nevertheless, some authors have suggested that oxidative stress could occur upstream (and not be the consequence) of iron-sulfur deficiency [116]. Undoubtedly, frataxin deficiency is reported to affect cell physiology at several levels, such as oxidative stress causing protein and DNA dysfunctions.…”
Section: Ros and Ataxiamentioning
confidence: 99%
“…The results shown here reveal that FDX1 levels are significantly below of those found in normal DRG neurons or in FA lymphoblastoid cells (Figs, 1 and S1) thus supporting the rationale that calcitriol supplementation should be able to recover cell survival after frataxin depletion. Although we are aware that the explanation on how frataxin deficiency results in decreased FDX1 levels remains to be answered, deficiency in Fe/S cluster-containing proteins has been observed in several models of the disease [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although a decrease in heme synthesis has been reported in yeast and mouse frataxin mutants [ 104 , 105 ], no alterations were observed in FA erythroid progenitor stem cells, thus suggesting alternative mechanisms able to overcome the frataxin-related defects [ 106 ]. Despite this, to date, the frataxin involvement in the ISC biosynthesis remains the most credited function of the protein [ 107 ]. Frataxin would directly interact with the complex formed by the cysteine desulfurase NSF1 and the iron–sulfur cluster assembly enzyme ISCU (the major components of the ISC synthesis machinery) [ 108 ], although it is not clear whether frataxin may act as iron donor [ 109 ] or as an allosteric regulator [ 110 ].…”
Section: Ferroptosis In Neurodegeneration and In Friedreich’s Ataxmentioning
confidence: 99%